Using Think-Pair-Share Strategy to Support Students in Speaking Lessons - Phan, Huyen; Lan , Do Thi My (Journal of English Language Teaching and Applied Linguistics, 2021)
Improving speaking skills plays an important role for anyone who pursues language proficiency, especially in the English language. While no one can contradict the fundamental value of this productive skill, speaking, as mentioned by Castillo (2007), poses challenges to students since it concerns complex constituents such as pronunciation, stress patterns, vocabulary or grammatical structures. Among countless cooperative strategies, Think-Pair-Share, proposed by Azlina (2010) can be regarded as a stimulating option to support students in improving their speaking capabilities. This study was set out to evaluate applying Think-Pair-Share strategy in the classroom to foster students’ speaking skills and engagement in speaking activities. 35 students in the AP (Advanced Program) at Thai Nguyen University of Economics and Business Administration (TUEBA) were chosen as target participants of the study. This research was anchored on a qualitative basis, and data were collected from three methods, including observation sheets, focus group and individual interviews, to ensure the principle of triangulation. Based on the findings, the researcher attempted to provide some modifications in applying the Think-Pair-Share technique so that it can be effectively exploited to give support to language learners in their speaking skills.